Determination of the optimal extrusion temperature of the PMMA optical fibers - Niedźwiedź, Malwina Julita; Gil, Małgorzata; Gargol, Mateusz; Podkościelny, Wiesław Marian; Mergo, Paweł (Photonics Letters of Poland, 2019)
The aim of this work was to determine optimal extrusion temperature for polymer optical fibers. For preliminary studies poly(methyl methacrylate) (PMMA) granulate was used. Samples of commercially available PMMA were subjected to four different temperatures in which were kept in oven for three different period of time. To examine the changes in the chemical structure of the polymer, an ATR-FT-IR (Attenuation Total Reflection Fourier Transform Infrared Spectroscopy) was chosen. Full Text: PDF References K. Peters, "Polymer optical fiber sensors—a review", Smart Mater. Struct. 20, 013002 (2011) CrossRef O. Ziemann, J. Krauser, P.E. Zamzow, W. Daum, "POF Polymer Optical Fibers for Data Communication" (New York, Springer-Verlag Berlin Heidelberg 2002). CrossRef M.A. van Eijkelenborg, M.C.J. Large, A. Argyros, J. Zagari, S. Manos, N.A. Issa, I. Bassett, S. Fleming, R.C. McPhedran, C. Martijn de Sterke, N.A.P. Nicorovici, "Microstructured polymer optical fibre", Opt Express 9, 319 (2001). CrossRef O. Çetinkaya, G. Wojcik, P. Mergo, "Decreasing diameter fluctuation of polymer optical fiber with optimized drawing conditions", Mater Res Express 5, 1 (2018). CrossRef P. Mergo, M. Gil, K. Skorupski, J. Klimek, G. Wójcik, J. Pędzisz, J. Kopec, K. Poruraj, L. Czyzewska, A. Walewski, A. Gorgol, "Low loss poly(methyl methacrylate) useful in polymer optical fibres technology", Phot. Lett. Poland, 5, 170 (2013). CrossRef J. Grdadolnik, "ATR-FTIR Spectroscopy: Its advantages and limitations", Acta Chim Slov. 49, 631 (2002). DirectLink P. Borowski, S. Pasieczna-Patkowska, M. Barczak, K. Pilorz, "Theoretical Determination of the Infrared Spectra of Amorphous Polymers", J Phys Chem A 116, 7424 (2012). CrossRef G. Socrates, "Infrared and Raman Characteristic Group Frequencies Tables and Charts" Third Edition (Baffins Lane Chichester, John Wiley & Sons Ltd 2001). DirectLink W. Schnabel, Polymer Degradation Principles and Practical Applications (Berlin, Akademie-Verlag 1981). DirectLink